Enhancing the human experience of learning with technology: new challenges for research into digital, open, distance & networked education - Palmeiro, Ricardo (2021)
The EDEN Eleventh Research Workshop – 21-23 October 2020 in collaboration with Universidade Aberta, LE@D, UAb, Portugal.